Konsep Diri Penyandang Tunanetra dan Implikasinya terhadap Layanan Bimbingan dan Konseling - Oktavia, Elvina; Zikra, Zikra; Nurfarhanah, Nurfarhanah (Universitas Negeri Padang, 2016)
Self-concept is an opinion, feeling or perception of someone about his/herself that is related to the physical appearance, social, emotional, moral, and cognitive. This research is based on the visual impairment people who judge themselves in negative way. This research uses quantitative method with descriptive approach. The subject of this research is 50 visual impairment people which consist of 30 blind people, and 20 low vision people. The instrument of this research is questionnaire. The result of this research shows that the self-concept of all of those visual impairment people are in the medium category. It is expected to all of guidance and counseling teachers to give their service based on the need of those people for keeping their self-concept good and helping to develop their self-concept in the positive way.